Incidence of venous thromboembolism following colorectal surgery - Lewis-Lloyd, Christopher A. (2023)
Colectomy is the second most common major abdominal operation globally with colorectal cancer (CRC) being the most common indication. Venous thromboembolism (VTE), comprising deep vein thrombosis and pulmonary embolism, is a potentially fatal yet preventable postoperative complication of which colectomy has one of the highest risks of any abdominal operation. However, perioperative care over the last two decades has changed with an increase in minimally invasive surgery and focus on VTE prevention. This has led to the introduction of international guidance advocating pharmacological VTE prophylaxis for a minimum of inpatient stay or 7-days following benign colectomy that extends to 4-weeks for those with CRC. Therefore, the aim of this thesis was to quantify changes in incidence rates of VTE following colectomy in relation to international changes in perioperative care and so help guide future improvements in VTE prevention.